ANALYSING GENERATION Z'S INTENTION TOWARDS USING ENVIRONMENT FRIENDLY DRINKING STRAWS: APPLYING AN EXTENDED THEORY OF PLANNED BEHAVIOUR - Manalu, Juan D. A; Rifai, Achmad P.; Abidin, Nur Balqishanis Zainal; Sari, Wangi Pandan (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2025)
The overuse of plastic straws has led to a considerable volume of plastic waste, posing a serious threat to the environment. This accumulation of plastic waste not only causes significant environmental pollution but also raises health concerns for both humans and animals. As an eco-friendly alternative to plastic straws, researchers have turned to environmentally friendly straws. To explore the factors influencing Generation Z's (Gen Z) adoption of these eco-friendly straws, this study utilizes the Theory of Planned Behaviour (TPB) while also incorporating environmental awareness and knowledge as additional determinants. Both quantitative using Partial Least Square – Structural Equation Model (PLS-SEM) and qualitative using thematic analysis methods are employed for comprehensive analysis. The results indicate that attitudes towards behaviour, perceived behavioural control, environmental awareness, and environmental knowledge all play pivotal roles in influencing the intensity of Gen Z's usage of environmentally friendly straws.